Analysis Of Hr Skill, Service, And Promotion Factors On Price That Influence The Level Of Sales Of Millenial Cafe Coffee - Nur Qinthara Jatnika, Ridhwan; Kustiawan, Unggul (Fakultas Ekonomi Universitas Gresik, 2023)
Coffee is one of the mainstay commodities in Indonesia's plantation sector. HR skills, service, promotion and price are factors that affect sales levels. This study aims to analyze the influence of HR skills, service, promotion on sales levels through price as mediation. The analysis was carried out by chance withdrawal of 250 respondents using the Questionaire method